DIRECTIONS OF BUSINESS DEVELOPMENT THROUGH PRIVATIZATION OF VACANT OBJECTS IN UZBEKISTAN - Khonova, Nodira Fazliddinovna (Journals Park Publishing, 2024)
In the article, the opinions of the world's leading scientists on the directions of business development through the privatization of vacant objects in Uzbekistan were studied, the main indicators of privatization were studied, the advantages and disadvantages of privatization and the methods of privatization of state property were analyzed, the revenues from the sale of state property were analyzed by region, and the vacant objects in Uzbekistan were analyzed. Reasoned conclusions and suggestions on directions for business development through privatization were developed, and recommendations for application in our country were given.
Keywords: privatization, business development, investment environment, enterprise, state property, business.